Penentuan Faktor Dominan yang Mempengaruhi Kualitas Jenis Varietas Padi Menggunakan Metode AHP - Tsaqib, Najmu; Magdalena, Hilyah; Septryanti, Ade (METIK JURNAL (AKREDITASI SINTA 3), 2025)
Abstract The quality of rice varieties is a crucial aspect in supporting food security and productivity of the agricultural sector. This study aims to identify the main factors that determine the quality of various rice varieties using the Analytical Hierarchy Process (AHP) method. This method was chosen because of its ability to process decisions systematically and structured. The factors analyzed include productivity, resistance to pests and diseases, planting period, quality of grain and rice, adaptation to the environment, and efficiency of production costs. Data were obtained through questionnaires and field surveys. The results of the analysis showed that resistance to pests and diseases was the most dominant criterion (24.8%), while superior varieties were the best choice with the highest weight (33.8%). This study is expected to be a reference for farmers and stakeholders in determining rice varieties that are appropriate to land conditions and local needs.